EFFECT OF APPLICATION OF ACCOUNTING AND INTERNAL CONTROL SYSTEM ON COOPERATION ACCOUNTABILITY IN PALU CITY - Nurhadi Nurhadi (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2018)
This study aims to examine and analyze the effect of the application of the accounting and internal control system, both simultaneously and partially to the accountability of cooperatives in palu. The data used in this research is data collected by distributing questionnaires on 62 cooperatives in the city of Palu, method of analysis used is multiple linear regression.Based on the analysis result of multiple linear regression can be summarized as follows: (1) Application of the accounting and internal control system simultaneously have a significant influence on the accountability of cooperatives in the city of Palu.(2) Application of the partial accounting has a significant influence on the accountability of cooperatives in Palu. (3) Internal control system partially have a significant influence on the accountability of cooperatives.